2022
DOI: 10.11124/jbies-21-00233
|View full text |Cite
|
Sign up to set email alerts
|

School-based obesity prevention programs in rural communities: a scoping review

Abstract: Objective: The objective of this review was to examine existing literature and conceptually map the evidence for school-based obesity prevention programs implemented in rural communities, as well as identify current gaps in the literature. Introduction: Pediatric obesity is a significant public health condition worldwide. Rural residency places children at increased risk of obesity. Schools have been identified as an avenue for obesity prevention in rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 121 publications
0
1
0
Order By: Relevance
“…Operating within the WSCC model, many programs have successfully engaged students, their peers, teachers, physical education instructors, nutritionists and community partners in large scale collaboration resulting in opportunities for systematic change [ 29 ▪▪ ]. Systematic reviews have shown that interventions directed at school-aged children and youth are most successful when they take place over at least 6 months and utilize a multipronged approach to tailor interventions based on age and developmental stage [ 30 ▪▪ ].…”
Section: Application Of School-based Health To Obesity and Type 2 Dia...mentioning
confidence: 99%
“…Operating within the WSCC model, many programs have successfully engaged students, their peers, teachers, physical education instructors, nutritionists and community partners in large scale collaboration resulting in opportunities for systematic change [ 29 ▪▪ ]. Systematic reviews have shown that interventions directed at school-aged children and youth are most successful when they take place over at least 6 months and utilize a multipronged approach to tailor interventions based on age and developmental stage [ 30 ▪▪ ].…”
Section: Application Of School-based Health To Obesity and Type 2 Dia...mentioning
confidence: 99%